Tantangan Dan Peluang Negara Asean Dalam Perbandingan Sumber Daya Manusia (SDM) Di Era Digital - Rivaldi, Dio; Dompak, Timbul (Prosiding, 2024)
The phenomenon currently occurring involves the challenges and opportunities faced by ASEAN countries in managing human resources (HR) in the digital era. These challenges include disparities in access to and utilization of Information and Communication Technology (ICT), disparities in education levels among member countries, and rapid changes in the job market's demands, which are increasingly focused on digital skills. This type of research employs quantitative research methods. The data source used in this study is panel data from 2019 to 2023 with variables including ICT (X1), Education (X2), and Economic Growth (Y). The data analysis technique used is multiple linear regression equation with the Least Squares method. The research findings indicate that the fixed effect model is the most suitable for use, based on the Chow test and the Hausman test, which show that all independent variables (X) in this study have a significant positive influence on the dependent variable (Y). The analysis results show a significant relationship between Information and Communication Technology (ICT) and economic growth in ASEAN countries. Thus, it can be concluded that ICT, education, and foreign direct investment are important factors that need to be considered in efforts to enhance economic growth in ASEAN countries. Efforts to improve ICT utilization and increase education levels have a positive impact on economic growth in the ASEAN region.